Target region oxygenation-based endovascular treatment in a chronic limb-threatening ischemia patient with multifocal arterial diseases - Unno, Naoki (J Vasc Surg Cases Innov Tech, 2020)
Patients with chronic limb-threatening ischemia often have multiple segmental diseases requiring revascularization. However, there is no defined milestone to indicate sufficient endovascular treatment (EVT). Using multiple near-infrared spectroscopic oximeters, we intraoperatively monitored regional tissue oxygen saturation (rSO(2)) to perform target region oxygenation-based EVT for a patient with chronic limb-threatening ischemia. Stent placement at the superficial femoral artery and angioplasty of the tibioperoneal trunk enabled rSO(2) in the target ischemic regions (dorsal foot and heel) to be >50% for ulcer healing. We herein describe target region oxygenation-based EVT with rSO(2) monitoring as an effective strategy for performing the minimum requisite procedures.